2022
DOI: 10.1021/acs.jpcc.2c06096
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light-Sensitive Debonding Layer for Reducing Adhesion of Polymer Adhesives for Recycling

Abstract: Separating adhesives from substrates is important for recycling metals and polymer materials used in a variety of applications such as food packaging and electronics. A proof-ofconcept self-assembled debonding layer for debonding adhesives on demand is developed in this research. The debonding layer is applied to a silica surface in three steps. These steps were characterized with sum frequency generation (SFG) vibrational spectroscopy, X-ray photoelectron spectroscopy (XPS), and contact angle goniometry. SFG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…According to its selection rule, SFG signals can only be detected from materials without inversion symmetry (under the electric dipole approximation). ,,, , Therefore, most cases the SFG signal can only be generated from surfaces/interfaces (with no inversion symmetry), not from the bulk media (which usually are centrosymmetric). Extensive previous research has demonstrated that SFG is a powerful technique to elucidate molecular structures and molecular interactions at buried interfaces in situ. , …”
Section: Introductionmentioning
confidence: 99%
“…According to its selection rule, SFG signals can only be detected from materials without inversion symmetry (under the electric dipole approximation). ,,, , Therefore, most cases the SFG signal can only be generated from surfaces/interfaces (with no inversion symmetry), not from the bulk media (which usually are centrosymmetric). Extensive previous research has demonstrated that SFG is a powerful technique to elucidate molecular structures and molecular interactions at buried interfaces in situ. , …”
Section: Introductionmentioning
confidence: 99%